A Full-Duplex MIMO System Based on CP-Free OFDM in Sensor Network. (11th July 2022) - Jiang, Hao; Chen, Hongming
Abstract : Recently, results have shown that full-duplex (FD) system based on orthogonal frequency division multiplexing (OFDM) is potential for wireless sensor networks. However, extending FD to further improve spectral efficiency by removing cyclic prefix (CP) with optimal canceling self-interference (SI) remains a challenge. In this paper, we analytically study the conventional FD OFDM system and proposed a CP-free system on this basis. The key point of the proposed scheme is the symbols transmitted in a unit of two identical symbols without CP. To eliminate the intersymbol interference, the disturbed part are replaced by the repeated signal at the receiver, which has the same effect as CP. Finally, an SI cancellation is down to restore the transmitted symbols. As a key of analysis, a multiple-input multiple-output (MIMO) FD simulation model is carried to show that our proposed scheme is effectiveness in terms of the bit error ratio (BER).